LINEARIZATION OF A GENERALIZED MATERIAL BALANCE EQUATION FOR COALBED METHANE RESERVOIRS - G PEÑUELA; A ORDOÑEZ R; A BEJARANO (CT&F Ciencia, Tecnología & Futuro, 1998)
A generalized material balance equation was presented at the Escuela de Petróleos de la Universidad Industrial de Santander for coal seam gas reservoirs based on Walsh 's method, who worked in an analogous approach for oil and gas conventional reservoirs (Walsh, 1 995). Our equation was based on twelve similar assumptions itemized by Walsh for his generalized expression for conventional reservoirs, it was started from the same volume balance consideration and was finally reorganized like Walsh (1 994) did. Because it is not expressed in terms of traditional (P/Z) plots, as proposed by King (1 990), it allows to perform a lot of quantitative and qualitative analyses. It was also demonstrated that the existent equations are only particular cases of the generalized expression evaluated under certain restrictions. This equation is applicable to coal seam gas reservoirs in saturated, equilibrium and undersaturated conditions, and to any type of coalbeds without restriction on especial values of the constant diffusion. En la Escuela de Petróleos de la Universidad de Santander se presentó una ecuación generalizada de balance en materiales para yacimientos de gas asociado al carbón teniendo como punto de partida el método aplicado por Walsh, quien trabajó en una expresión similar pero para yacimientos convencionales de petróleo y gas (Walsh, 1995). Esta ecuación se fundamentó en doce suposiciones similares a las hechas por Walsh en su expresión generalizada para yacimientos convencionales, parte de la misma consideración volumétrica y finalmente se reorganiza como lo realizaron Walsh et al (1 994). Al no ser expresada en términos de los gráficos (P/Z) planteado por King (1 990), da pie para hacer un mayor número de análisis cuantitativos y cualitativos. Además se mostró que las ecuaciones existentes son solo casos particulares de la generalizada evaluada bajo ciertas restricciones. Esta ecuación es aplicable a yacimientos en estado saturado, equilibrio y subsaturado, y para cualquier manto de carbón sin restricciones para valores especiales de la constante de difusión.